Relative percentage of protein partitioned into various protein fractions prepared by ammonium sulphate precipitation of ovarian follicular fluid in buffaloes* - Gupta, P S; Ravindra, J P; Reddy, G R (The Indian Journal of Animal Sciences, 2005)
Follicular fluid consists of many proteins that influence oocyte maturation. fractionation of ovarian follicular fluid into different protein fraction is the first step in the isolation ofpeptides/proteins. In this study. bubaline ovarian Follicular fluid collected from different size categories of follicles (small, medium and large) was fractionated with ammonium sulphate precipitation at different saturation levels into different protein fractions (A to G). The amount ofprotein in each fraction and relative percentage of total protein partitioned into different protein fractions was estimated. The amount of protein partitioned in to different fractions of follicular fluid varied significantly in any particular category of follicles. There was significant difference among different categories of follicles with respect to the peptide level/relative percentage of protienc partitioned into a particular fraction. By 95% of ammonium sulphate saturation. 81 and 78% of the protein quantity in the fbllicular fluid of small and large follicles, respectively, got precipitated but in the medium size follicles, only 45% of the protien quantity got precipitated. It may be because of the variation in the type of proteins or quantity of specific protein present in diffrrent size categories of follicles. The data presented may give an idea about the quantum of protein that can be obtained from different protein fractions of the fluid that facilitates effective planning of the strategies for the isolation and partification of specific peptides of ovarian follicular fluid in buffaloes.